EVALUASI PENGELOLAAN LIMBAH KLINIS TAJAM DI RSUD KABUPATEN CILACAP - Agnes Fitria Widiyanto Sistiarani; Siti Nurhayati; Ery Wahyuningsih (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT The hospital was the institution of the health service with the core of the preventive service activity, curative, rehabilitatif and pro-the motive. This activity will cause the positive and negative impact. The positive impact was the increase in the level of the health of the community, whereas the impact of his negative in part was the waste and the medical waste and non medical that could cause the illness and pollution that must be attentive especially.The research was carried out qualitatively with the case study plan. The research was carried out in RSUD Kabupaten Cilacap. The data collection was carried out by means of observation and the interview.Results of the research of showing that the liquid waste management in Pertamina UP IV Cilacap went were good enough with was supported by human resources (human resources), the fund, the method, material, the legislation regulation and the guidance of the implementation and the technical guidance. In order to increases the management system must be increased by the quality of human resources that handled the clinical waste sharply. key words: evaluation, clinical waste, management, hospital Kesmasindo, Volume 6, (3) Januari 2014, Hal. 183-193